2016
DOI: 10.1016/j.jtcvs.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Surgical team turnover and operative time: An evaluation of operating room efficiency during pulmonary resection

Abstract: Active management of surgical team turnover may be an opportunity to improve operating room efficiency when the surgical team is engaged in a major pulmonary resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Reductions in this have knock-on effects of reduced waiting lists and reduced cost per operation. Furthermore, it has been linked to lower risk of perioperative adverse events and improved patient satisfaction 12. It is shown that longer operative times correlate with increased risk of complications and longer postoperative recovery 13.…”
Section: Barriers To An Effective Teammentioning
confidence: 99%
“…Reductions in this have knock-on effects of reduced waiting lists and reduced cost per operation. Furthermore, it has been linked to lower risk of perioperative adverse events and improved patient satisfaction 12. It is shown that longer operative times correlate with increased risk of complications and longer postoperative recovery 13.…”
Section: Barriers To An Effective Teammentioning
confidence: 99%
“…Several studies have shown that the experience and distinctive character of the individual surgeon or the surgical team in uences the duration of the operative duration [14,15,16]. The current studies illustrate that Operative duration is longer in the presence of junior surgical trainees, which may re ect both the procedural learning curve as well as potential confounding due to referral of complex surgical cases to senior attending supervision.…”
Section: Discussionmentioning
confidence: 57%
“…Many factors affected the turnover time including an inefficient central processing of instruments or a multidisciplinary problem involving nursing, anesthesia, housekeeping and the turnover team staff not working in co-ordination [9]. Active management of surgical team turnover may be an opportunity to improve operating room efficiency [10]. In our study, an instructional supervision program by an operating room assistant was conducted to significantly reduce turnover time.…”
Section: Discussionmentioning
confidence: 98%